A Structuralist Study of the Poem "The Final Ends..?!..I Wish" by the Poet Fayez Khadour (Journal of Hama University, 2021)
The research gives a textual reading based on what is known in the contemporary critical tradition as the theory of levels in the structuralist philosophy, and it is a reading that defines these levels as follows: the linguistic level, the pictorial level, and the rhythmic level. And it should be noted that the semantic level overlaps with these levels as a compendium of what the text aims to say, based on the systems and formats that lead to its production.Perhaps the most notable result of the research is its defence of the idea of the evolution of structuralist reading in practice, by the development of the stages that the structuralism has gone through on the formal, structural, and psychological levels. This is based on the conviction that structural analysis is applied in critical practice as a conventional procedure, without necessarily adopting purely structural sayings and procedural tools, for attention to what is within the text has been critically at the centre of the structuralist approach. As for the development to which we have referred to, it has appeared through the effect of the textual thresholds in activating the mechanism of reception, on the basis that these thresholds are components of the text, and of its linguistic texture; they are part of the text and lie within, not outside, it.